Pengaruh Motivasi Kerja, Religiuitas Dan Tacit Knowledge Terhadap Kinerja Karyawan (Studi Kasus Pada CV. Makin Jaya Mojokerto) - Masrur, Moh Ubaidillah; Asiyah, Siti; Ramadhan, Tri Sugiarti (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract The purpose of this study is to test and analyze the influence of work motivation, religiosity and tacit knowledge on employee performance at CV. Makin Jaya. This type of research is quantitative, namely the data can be obtained using a questionnaire technique. The population in this study were all employees of CV. Makin Jaya with a total of 60 employees. In this study, the sample to be taken was all employees of CV. The results of the study indicate that work motivation, religiosity and tacit knowledge simultaneously have a significant effect on employee performance. Work motivation has a positive and significant effect on employee performance. Religiosity has a positive and significant effect on employee performance. Tacit knowledge has a positive and significant effect on employee performance. Keywords: Motivation, Religiosity, Tacit Knowledge And Employee Performance